Prenatal ultrasonographic findings of adhesion-membrane complex and its relation with obstetric history. (2nd January 2021) - Hocaoglu, Meryem; Batukan, Cem; Yuksel, Atil
Abstract: Background: Intrauterine adhesions are usually detected incidentally during routine obstetric ultrasound and remain one of the reasons for concern for both clinicians and patients. Objective: Our objective was to document ultrasonographic findings of intrauterine adhesions detected in obstetric ultrasound and to investigate their correlation with obstetric history. Study Design: Detailed scans were performed in 685 singleton pregnancies at 16–24 weeks' gestation. Intrauterine adhesion was referred to as "adhesion-membrane complex'' (AMC). Patients were divided into three groups: Group I consisted of patients with ≥1 therapeutic D&C associated with pregnancy but with neither vaginal delivery nor Cesarean section (CS). Group II consisted of patients with ≥1 CS but with neither vaginal delivery nor therapeutic D&C associated with pregnancy. Group III consisted of patients who were in their first pregnancy. Ultrasonographic properties of AMC and relationship between AMCs and obstetric history were investigated. Results: The incidence of AMC in Group I ( n = 108), Group II ( n = 189), and Group III ( n = 388) was 11.1% ( n = 12), 1.05% ( n = 2) and 1.03% ( n = 4), respectively. Positive history of D&C is associated with significantly increased risk of AMC (risk ratio:10.778; 95% confidence interval: 3.55–32.75). Also, previous history of CS is not associated with significantly increased risk of AMC (risk ratio: 1.026; 95% confidence interval: 0.19–5.55). The AMCs were located in the upper half in 7 (38, 9%) and in the lower half of the uterus in 11 (61.1%) patients. The midpoint thickness of the AMC was between 0.75 and 5.10 mm (mean: 2.65 mm; SD ± 1.2). The width of the AMC was between 2 and 52 mm (mean: 20.98; SD ± 15.3), the heights of the AMCs were 5–60 mm (mean: 33.27 mm; SD ±17.0). In ten of the AMC positive patients (55.6%) a thick and bulbous free end and in eleven of them (61.1%) a "Y image" was detected. The mean gestational age at birth was 37.4 (SD ± 3.3) weeks in 18 patients with AMC. There were no intrauterine fetal or perinatal deaths. None of the neonates had congenital abnormalities. Conclusions: Intrauterine adhesions detected in obstetric ultrasonography were redefined and renamed in a more comprehensible manner. Our results pointed out that while the positive history of D&C is associated with significantly increased risk of AMC, previous history of CS is not associated with significantly increased risk of AMC.